2011
DOI: 10.1111/j.1365-2672.2011.04942.x
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia colisurvival in lettuce fields following its introduction through different irrigation systems

Abstract: Aims:  This study aimed to assess the contamination risk of Escherichia coli in commercial lettuce grown under three different irrigation systems (overhead sprinkler, subsurface drip and surface furrow). Methods and Results:  Three replicated field trials were conducted. In an initial trial, we consistently observed higher mesophilic bacteria counts under sprinkler irrigation but visual quality was found to be dependent on the water potential of leaves at harvest. Further, in the other two trials, E. coli K‐12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 38 publications
2
59
0
4
Order By: Relevance
“…Water has been iden-tified as a major reservoir for pathogens and irrigation as a vehicle for transmission of pathogens to fields and produce (12,30,41,(72)(73)(74)(75). L. monocytogenes is often found in various water sources, with reported prevalence from Ͻ1% to 29% (14,76,77).…”
Section: Field Practices Associated With Presence Of Pathogensmentioning
confidence: 99%
“…Water has been iden-tified as a major reservoir for pathogens and irrigation as a vehicle for transmission of pathogens to fields and produce (12,30,41,(72)(73)(74)(75). L. monocytogenes is often found in various water sources, with reported prevalence from Ͻ1% to 29% (14,76,77).…”
Section: Field Practices Associated With Presence Of Pathogensmentioning
confidence: 99%
“…Irrigation water is considered a potentially important introduction route, and several studies have shown its potential for the transmission of enteric pathogens to lettuce plants. However, most of these studies were conducted either under laboratory or controlled conditions in growth chambers (Brandl and Mandrell, 2002;Solomon et al, 2003;Aruscavage et al, 2008;Aruscavage et al, 2010;Brandl and Amundson, 2008;Zhang et al, 2009;Erickson et al, 2010a) or field experiments (Barker-Reid et al, 2009;Erickson et al, 2010b;Harapas et al, 2010;Wood et al, 2010;Fonseca et al, 2011). Few studies have compared both types of experimental setups.…”
mentioning
confidence: 99%
“…Em áreas de produção agrícola, destacam-se como fatores que reduzem a qualidade das águas superficiais e subterrâneas, o cultivo e manejo do solo e o uso sucessivo de agrotóxicos, fertilizantes, despejos residuais urbanos e industriais e adubos orgânicos, que causam acúmulo de metais potencialmente tóxicos (MPT) e contaminação bacteriológica por (coliformes totais e fecais) nos ecossistemas aquáticos e terrestres (CHEN et al, 2006;FONSECA et al, 2011;HANI;PAZIRA, 2011).…”
Section: Introductionunclassified
“…O aumento considerável do número de patógenos nos corpos hídricos na área de produção agrícola ocorre principalmente pelo escoamento de esgotos domésticos e sistemas sépticos, como fossas, ricas em excretas humanas ou pela ação das chuvas (CRAUN et al, 2010;FONSECA et al, 2011).…”
Section: Introductionunclassified